Rehabilitative Treatment as an Alternative in Amputee Patients. Case Report and Literature Review - Ismaray Sacerio González; Elohilda de la Caridad Cruz Jiménez; Silvia Georgina de la Torre Castellanos (Revista Finlay)
The amputation or separation of a part of the body, of a lower or upper limb, is a surgical procedure that entails important anatomical, functional, psychological and social consequences. The authors were motivated to present a case from the Specialized Outpatient Center of the Cienfuegos province, with the objective of describing the experience during the combination of rehabilitative treatment and natural and traditional medicine in a patient with amputation of the left lower limb. The case of a 52-year-old male patient is presented, with a history of type 2 diabetes mellitus and arterial hypertension controlled by treatment, in addition to suffering from hereditary thrombopathy treated with anticoagulants, which is why he underwent surgical treatment. The combination of rehabilitative treatment and natural and traditional medicine in patients with chronic diseases with amputation of the left lower limb is an action of motor and functional conditioning to achieve their return to daily life. The case is presented because the combination of rehabilitative treatment and natural and traditional medicine in a patient who suffers from several chronic diseases is interesting.